A dissipative model for deep-drawing simulations: Elastic springback prediction and incremental forming strategies. (October 2021) - Denis, Y.; Hamila, N.; Itskov, M.; Guzman-Maldonado, E.; Morestin, F.
Abstract: In industrial applications, with geometries of fabric and textile composites becoming more and more complex, new deep drawing strategies are required. In this context, modern incremental forming strategies appear to be very advantageous. Moreover, recent approaches have emerged making it possible to reach decent conclusions about the incremental forming strategy and the ability to predict the elastic spring back as well as the residual stresses in a draped woven fabric. The aims of this paper were thus several. The first part presents a discussion of the differences between classical models (often hyperelastic) and new ones (dissipative, hysteretical) under large strains. Subsequently, these models were compared in application to different deep-drawing geometries. It was found that more sophisticated models were interesting for complex forming, while common hyperleastic ones were efficient enough for simple geometries. The last part introduces some results concerning spring-back and new capabilities obtained by such dissipative models. Finally, two incremental forming tool geometries were also presented and discussed.